Vector theory of diffraction by gratings made of a uniaxial dielectric-magnetic material exhibiting negative refraction - Depine, Ricardo Angel (2006)
Diffraction of linearly polarized plane electromagnetic waves at the periodically corrugated boundary of vacuum and a linear, homogeneous, nondissipative, uniaxial dielectric-magnetic material is formulated as a boundary-value problem and solved using the differential method. Attention is paid to two classes of diffracting materials: those with negative definite permittivity and permeability tensors and those with indefinite permittivity and permeability tensors. The dispersion equations turn out to be elliptic for the first class of diffracting materials, whereas for the second class they can be hyperbolic, elliptic, or linear, depending on the orientation of the optic axis. When the dispersion equations are elliptic, the optical response of the grating is qualitatively similar to that for conventional gratings: a finite number of refraction channels are supported. On the other hand, hyperbolic or linear dispersion equations imply the possibility of an infinite number of refraction channels. This possibility seriously incapacitates the differential method as the corrugations deepen. © 2006 Optical Society of America.